DNP-KLH Yields Changes in Leukocyte Populations and Immunoglobulin Isotype Use with Different Immunization Routes in Zebrafish - Weir, Heather; Chen, Patricia L.; Deiss, Thaddeus C.; Jacobs, Natalie; Nabity, Mary B.; Young, Matt; Criscitiello, Michael F. (Frontiers in Immunology, 2015)
Distinct methods are required for inducing mucosal versus systemic immunity in mammals for vaccine protection at the tissues most commonly breached by pathogens. Understanding of mucosal immunization in teleost fish is needed to combat aquaculture disease, understand emerging ecological threats, and know how vertebrate adaptive immunity evolved. Here we quantitatively measured expression levels of IgM as well as the teleost mucosal immunoglobulin, IgZ, in zebrafish given an antigen systemically via intraperitoneal (i.p.) injection or mucosally via bath immersion. Both immunoglobulin isotypes and the B cell activating factor (BAFF) gene transcription was induced in fish injected with antigen as compared to saline injected or antigen immersed fish. We provide here reference hematology for this model species, and differential blood counts revealed a greater lymphocyte percentage in both i.p. and immersed fish, with large lymphocyte counts reaching statistical significance. These humoral adaptive gene transcription and cytological data should provide a foundation for more studies connecting immunology in this dominant developmental and genetic fish model to other species where mucosal immunization is of greater commercial importance.